(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article examines the improvement of teaching methodology in the field of medical information technologies through the systematic use of digital educational resources. The rapid digital transformation of healthcare and higher education requires the modernization of instructional approaches aimed at developing students’ professional competencies in medical informatics, health information systems, and digital healthcare technologies. The study analyzes the pedagogical potential of digital learning platforms, interactive simulators, virtual laboratories, and multimedia content in enhancing the effectiveness of teaching and learning processes. The research is based on a mixed-methods approach that combines comparative analysis of traditional and digital teaching models, expert evaluation of instructional materials, and assessment of students’ learning outcomes. Special attention is given to the integration of learning management systems, adaptive educational technologies, and competency-based instructional design in medical IT education. The results demonstrate that the structured application of digital educational resources significantly improves students’ motivation, cognitive engagement, and practical skill formation. The proposed methodological framework contributes to the development of a flexible and student-centered learning environment that meets the requirements of digital healthcare and modern medical education. The findings may be used in curriculum design, teacher training, and the development of digital learning strategies for medical and technical universities